The Fight Against Human Trafficking in Indonesia’s Fisheries Industry - Mokhamad Saiful Farisin; Alvina Putri Fazha (Jurnal Lemhannas RI, 2024)
Purpose: This study seeks to explore Indonesia's initiatives to combat human trafficking, particularly within the fisheries industry, which poses a significant threat to national security. Furthermore, Indonesia's national reputation is jeopardized by the Benjina case, which has garnered international scrutiny. This situation also threatens national resilience, especially if local fisheries products are subjected to boycotts in the global market. Study Design/Methodology/Approach: Employs the 4Ps framework—comprising Prevention, Protection, Prosecution, and Partnership—as a lens through which to analyze Indonesia's initiatives in combating human trafficking. Furthermore, this research adopts a qualitative methodology, drawing upon secondary data to systematically map the measures that have been implemented in this specific industry Findings: Indonesia's initiatives have successfully met at least half of the indicators in each category of the framework. However, several challenges persist, including the lack of specific legislation addressing cases within this industry and the absence of reports on programs. This makes it challenging to evaluate their effectiveness.Top of FormBottom of Form Originality/Value: The 4Ps framework serves as a global benchmark for assessing the initiatives undertaken by countries to combat human trafficking. However, the scarcity of literature surrounding this framework presents a significant gap in existing research. This analysis offers valuable insights for policymakers, encouraging reflection on the programs that require sustainable implementation and further development to enhance the effectiveness of efforts against human trafficking.